The Effect of Perception of Usefulness, Perception of Ease of Use, Intention to Use on the Use of the M-Passport Application at the Class I Immigration Office, Special TPI, Makassar: JEL Classification: H83, O33, O38, M15 - Budi Prasetya; M. Nasir Hamzah; Nurmadhani Fitri Suyuthi (Journal of Management and Administration Provision, 2026)
The objectives of this study are 1) To analyze and examine the effect of Perceived Usefulness on the use of the M-Paspor application at the TPI Makassar Class I Special Immigration Office. 3) To analyze and examine the effect of Perceived Usefulness on the Intention to Use the M-Paspor application at the TPI Makassar Special Class I Immigration Office. 4) To analyze and examine the effect of Perceived Ease of Use on the Intention to Use the M-Paspor application at the TPI Makassar Special Class I Immigration Office. 5) To analyze and examine the effect of Intention to Use on the use of the M-Paspor application at the TPI Makassar Special Class I Immigration Office. The research approach used is quantitative-descriptive. This study was conducted at the TPI Makassar Special Class I Immigration Office, with the research subjects being passport applicants at the office, and a total sample size of 102 respondents. Data collection techniques included observation, questionnaires, and documentation. The findings show that Perceived Usefulness has a significant effect on the use of the M-Paspor application. Perceived Usefulness also has a significant effect on the Intention to Use the M-Paspor application. Perceived Ease of Use has a significant effect on the use of the M-Paspor application. Perceived Ease of Use also has a significant effect on the Intention to Use the M-Paspor application. Furthermore, Intention to Use has a significant effect on the use of the M-Paspor application.